Alternative solar water heater for domestic purpose - Sadrin, Samara; Hossain, Maherin; Mohith, Ehsanul (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electronics and Communication Engineering, 2009.